Analisis Kebutuhan Lahan Berdasarkan Distribusi Sebaran Penduduk di Kabupaten Mamuju - Radinal Jayadi (Prodi PWK Universitas Tadulako, 2026)
An analysis of land requirements based on population distribution in Mamuju Regency is essential for evaluating sectoral policies that influence spatial utilization and agrarian resource management. This study aims to provide an evaluative foundation for the revision process of the 2025 Regional Spatial Plan (RTRW) of Mamuju Regency, ensuring that the future direction of spatial structure and land‐use patterns can be formulated more comprehensively and responsively to existing conditions. The analytical methods employed include assessing land availability for cultivation activities and mapping population distribution across zones categorized as available and unavailable for such utilization. The findings indicate that land availability for cultivation activities in Mamuju Regency covers 1,215 km², while 3,736 km² are classified as unavailable, including designated protected areas. Of the total population, 259,539 residents occupy areas where land is available for utilization, whereas 29,520 residents live in areas categorized as unavailable, most of which fall within protected zones as defined by the RTRW. These results underscore the need to evaluate policies related to protected area designation and enhance the inventory of land tenure within forest areas that serve as objects of agrarian reform, including the redistribution of land to local communities. Accordingly, the utilization of agrarian resources in Mamuju Regency is expected to proceed more effectively, efficiently, and sustainably, while maintaining a balance between development needs and environmental conservation.